Pengaruh Promosi, Citra Merek, dan Potongan Harga terhadap Minat Beli Produk Fashion UMKM : Studi Kasus pada Toko Hijab By Aida Kudus - Dwi Nastrilia, Maula; Septiyanti, Dwi; Choirun Nisa, Alfi; Andni, Riyan; Candra, Eki (Lembaga Pengembangan Kinerja Dosen, 2025)
Abstract. There are undoubtedly a lot of things that influence consumers' desire to purchase, such as price breaks, brand perception, and promotions. Consumers' interest in purchasing items starts with their attention, which is followed by interest, desire, and action, all of which eventually result in the purchase of the product. However, other influences like other people's opinions and unanticipated events that necessitate purchasing can have an impact on buying interest. The goal of this study is to determine and examine the impact that price reductions, brand image, and promotions have on consumers' desire to purchase goods from the Hijab by Aida Kudus Shop. This study takes a causality research strategy and use descriptive quantitative tools. A questionnaire was employed in the sample approach with a population of Hijab Shop customers by Aida Kudus. Using the SPSS version 26 analysis tool, the accidental sampling approach was used to get samples for this study. This method was based on Slovin's hypothesis. Despite the effects of other variables not considered in this study, the findings indicate that the three binding variables promotion, brand image, and price reductions have a positive and significant impact on the dependent variable, which is buying interest.